Inpatient Treatment of Patients Admitted for Dizziness: A Population-Based Healthcare Research Study on Epidemiology, Diagnosis, Treatment, and Outcome. Issue 10 (December 2017) - Renner, Vera; Geißler, Katharina; Boeger, Daniel; Buentzel, Jens; Esser, Dirk; Hoffmann, Kerstin; Jecker, Peter; Mueller, Andreas; Radtke, Gerald; Axer, Hubertus; Guntinas-Lichius, Orlando
Abstract : Objective: To determine inpatient treatment rates of patients with dizziness with focus on diagnostics, treatment and outcome. Study Design: Retrospective population-based study. Setting: Inpatients in the federal state Thuringia in 2014. Patients: All 1, 262 inpatients (62% females, median age: 61 yr) treated for inpatient dizziness were included. Main Outcome Measures: The association between analyzed parameters and probability of improvement and recovery was tested using univariable and multivariable statistics. Results: Final diagnosis at demission was peripheral vestibular disorder (PVD), central vestibular disorder (CVD), cardiovascular syndrome, somatoform syndrome, and unclassified disease in 75, 9, 3, 0.6, and 13%, respectively. The most frequent diseases were acute vestibular neuritis (28%) and benign paroxysmal positional vertigo (22%). The follow-up time was 38 ± 98 days. 88.5% of patients showed at least an improvement of complaints and 31.4% a complete recovery. The probability for no improvement from inpatient dizziness was higher if the patient had a history of ear/vestibular disease (hazard ratio [HR] = 1.506; 95% confidence interval [CI] = 1.301–1.742), and was taking more than two drugs for comorbidity (HR = 1.163; CI = 1.032–1.310). Compared with final diagnosis of cardiovascular syndrome, patients with PVD (HR = 1.715; CI = 1.219–2.415) and CVD (HR = 1.587; CI = 1.076–2.341) had a worse outcome. Conclusions: Inpatient treatment of dizziness was highly variable in daily practice. The population-based recovery rate was worse than reported in clinical trials. We need better ways to implement clinical trial findings for inpatients with dizziness. Abstract : Supplemental Digital Content is available in the text